Coronary arteries in the fetal heart – a pictorial review - Respondek-Liberska, Maria (Prenatal Cardiology, 2023)
Coronary arteries (CA) in the fetal heart are seen very rarely. However, due to the introduction of the latest ultrasound technology, they can be seen in the late third trimester of pregnancy, regardless of the heart anatomy. Fetal haemodynamics can be analysed during fetal echocardiography not only in fetuses with fetal growth restriction, but also in normal fetal growth. Visualization of fetal coronary artery flow may have a temporary nature and therefore may suggest possible fetal heart compensation mechanisms. In the case of visualization of coronary artery by colour Doppler, pulse wave Doppler is recommended for the analysis of maximal velocity and direction of blood flow.